2022
DOI: 10.3389/fendo.2022.876067
|View full text |Cite
|
Sign up to set email alerts
|

Role of the major histocompatibility complex class II protein presentation pathway in bone immunity imbalance in postmenopausal osteoporosis

Abstract: Bone immunity regulates osteoclast differentiation and bone resorption and is a potential target for the treatment of postmenopausal osteoporosis (PMOP). The molecular network between bone metabolism and the immune system is complex. However, the molecular mechanism underlying the involvement of the major histocompatibility complex class II (MHC-II) molecule protein presentation pathway in PMOP remains to be elucidated. The MHC-II molecule is a core molecule of the protein presentation pathway. It is combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Notably, OP is often linked with chronic inflammatory conditions [ 43 ]. The decline in estrogen during menopause and aging-related changes are known to exacerbate OP by enhancing osteoclastogenic inflammatory cytokine production [ 44 ]. Inflammatory rheumatic diseases, which involve both local and systemic bone loss, serve as prime examples of the deep-seated interplay between the immune system and bone health, often leading to osteoclast hyperactivation and a disrupted balance in bone dynamics [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, OP is often linked with chronic inflammatory conditions [ 43 ]. The decline in estrogen during menopause and aging-related changes are known to exacerbate OP by enhancing osteoclastogenic inflammatory cytokine production [ 44 ]. Inflammatory rheumatic diseases, which involve both local and systemic bone loss, serve as prime examples of the deep-seated interplay between the immune system and bone health, often leading to osteoclast hyperactivation and a disrupted balance in bone dynamics [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MHC-II molecule is a central molecule in the protein presentation pathway. It binds to processed short peptides and presents them to T lymphocytes, activating them to become effector T cells [ 54 ]. Abcouwer et al [ 55 ] Minocycline was particularly effective in decreasing the appearance of MHCII+ inflammatory leukocytes and reduced leukocyte adhesion and invasion, as well as vascular permeability in RIR.…”
Section: Discussionmentioning
confidence: 99%
“…The M2 phenotype is selectively activated macrophages.It is involved in osteogenic metabolism by stimulating bone marrow mesenchymal stem cells to differentiate into OBs. The M1 and M2 phenotypes are usually associated with bone catabolism and anabolism, respectively (10,11). One study showed that M1/M2 macrophage ratio increased in OVX osteoporosis mouse model (26), reflecting that estrogen deficiency mediated macrophage ratio changes may be closely related to osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although OP is still considered an endocrine disease, a growing number of studies now show that it is closely related to immune and inflammatory states (9)(10)(11). Since bone and the immune system share a common developmental niche, the developmental remodelling of bone is affected by the immune system, and innate and adaptive immune cells can participate in the pathogenesis of OP by producing proinflammatory mediators (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation